Experimental poisoning in cattle by Asclepias curassavica - Tokarnia, Carlos Hubinger; Dobereiner, Jorgen; Canella, Camillo F. C. (Pesquisa Agropecuaria Brasileira, 2014)
Experiments with the aerial parts of Asclepias curassavica L., administered orally to bovines, were made. There are many references about its toxicity, but only few data on experimental poisoning by this plant in cattle. The green fresh plant was given to 38 young bovines, in different amounts and at different periods of the year; some animals received the plant more than once. Symptoms of poisoning, which were observed from 5 g/kg bodyweight on, consisted mainly in loss of appetite, diarrhea, tympany, submaxillar edema and cardiac irregularities; these symptoms lasted one to few days, and when the animals did not die, they always recovered in a short time. In the three animals that died during the experiments, the most important post-mortem finding was bloat. Histopathologic examinations did not reveal consistent and characteristic changes. There was no development of tolerance nor any accumulative effects due to the ingestion of the plant. Based on their field studies and on their experiments, the authors conclude that spontaneous poisoning by A. curassavica in cattle is not likely. The plant apparently is relatively unpalatable, animals do not eat it, even when hungry and on overgrazed pastures during the dry season.